Investigating the relationship between the monetary policy shock through the exchange rate channel on the management quality index in the banking system: by examining the productivity approach - Farhad Sharifi Bagha; Jafar Haqiqat; Zahra Karimi Takanloo (مدیریت بهره وری)
Abstract The purpose of the current research is to investigate the relationship between the monetary policy shock via exchange rate channel on the management quality index in the banking system within a productivity approach. The current research is applied in terms of its purpose and analytical-descriptive in terms of its method. This study utilizes 96 variables of seasonal time series data that affect the management quality index within the bank productivity framework, one of the critical indicators for assessing the health of the banking system. The analysis covers the period from 1378:1 to 1401:4 and employs the Factor-Augmented Vector Autoregression (FAVAR) model to investigate the effect of monetary policy via exchange rate channel on the management quality index in the banking system. Among the many variables influencing the productivity of the whole bank, which are extracted from the bank's balance sheet, the amount of expenses (financial expenses, administrative and general expenses) and the amount of profit (net investment interest, interest received from foreign currency deposits) were investigated. The results indicated that the monetary policy shock through the exchange rate channel had a significant negative relationship with the selected variables and caused a decrease in the amount of profit and an increase in the amount of expenses, which led to a decrease in the overall productivity of the bank.   Key Words: management quality in the banking system, productivity approach, monetary policy shock, exchange rate 1.Introduction Productivity is one of the concepts of economics and management, which is defined as: "the amount of goods or services produced compared to each unit of energy or labor spent without reducing quality”, in other words "effectiveness along with efficiency". In the operational concept, productivity is the ratio between output values ​​and input values ​​used in the production process. In fact, the purpose of productivity is to maximize output and minimize input. On the other hand, one of the most important challenges of the banking system in any economy is its reaction to shocks and economic fluctuations. Any unexpected phenomenon that has an unpredictable effect on economic variables is considered a shock, which can be classified as environmental, external, internal or supply and demand shocks. The adoption of monetary policies is the process by which the central bank or the country's monetary authority controls the supply of money or other monetary variables and imposes fluctuations on the economy as a type of economic policies. 2.Literature Review Sofin (2005) in a study entitled “the source of changes in profitability in commercial banks in developing countries; The case study of the country of Malaysia” has investigated the productivity of all production factors in commercial banks in Malaysia during the period from 1998 to 2003 using the Malmquist index. In this study, the interest income of the banks from the place of granting various types of facilities, the amount of loan paid as the bank's income and the volume of various types of bank deposits, labor force and fixed assets of the bank's branches were taken into consideration. In total, the results of this study showed that the productivity of production factors in Malaysian banks decreased by 7% during the period under review. The negative effects of technological changes have been one of the reasons for the decrease in the productivity of banks. In a study, Sanbat (2016) has investigated monetary policy transmission channels in the United States using the FAVAR model and 154 monthly time series variables in the time period from 1970 to 2014. To this end, the effect of monetary policy shock on bank portfolio variables and economic activity variables and the effect of lending on economic activity variables have been investigated. The research findings indicate the existence of a credit channel in America. Also, it was found that the contractionary monetary policy causes a decrease in loan supply, which leads to a dcrease in economic activities. Elborn et al. (2019) in a study aimed at Do SVARs detect unconventional monetary policy shocks? revealed that the used identification schemes fail to recover real unconventional monetary policy shocks in the Eurozone. In their identification schemes, information on the size of the central bank's balance sheet is key to distinguishing monetary policy shocks from other shocks that reduce financial market stress. In the present study, we show that replacing ECB balance sheet size with random numbers leads to statistically indistinguishable shock response functions and time series of abnormal monetary policy shocks. In contrast, using monetary policy shocks identified by forward rate data by Jaroski and Karadi, we argue that unconventional monetary policies have not had a statistically significant effect on real economic activity. 3.Methodology Regarding the purpose, the present study is applied research, utilizing an analytical-descriptive methodology. The FAVAR or the Factor-Augmented Vector Autoregression model presented by Bernanke, Boivin and Elias (2003) has been used to solve the problems related to the VAR model. Therefore, using 96 variables of seasonal time series data affecting the management quality index within the bank productivity approach which is one of the most important indicators of assessing the health of the banking system, and employing the factor-added empirical model (FAVAR), the effect of monetary policy via the exchange rate channel on the management quality index in the banking system was investigated during the period of 1378:1-1401:4 In order to investigate the mechanism of the impact of monetary policy shocks via exchange rate channel on the variables affecting the health of the banking system, the two-stage method of principal components was used. Therefore, first, the following equation was estimated without considering the Yt vector, based on which the number of optimal factors was selected. The equation can be written using model variables as follows: After determining the number of optimal factors, the equation was estimated. This equation can be shown as follows: 4.Result The purpose of the current research was to investigate the relationship between the monetary policy shock through the exchange rate channel on the management quality index in the banking system within the productivity approach. Regarding the relationship between the variables, it was expected that the value of each variable from the previous period will have a positive effect on the current value of the variable, in such a way that, for example, an increase in the exchange rate in the past period increases or decreases the variables in the current period. The monetary policy through the exchange rate channel has led to a direct effect on the deposits of the banking network and, as a result, the power to grant facilities and operational income, which, in turn, affects one of the most important indicators of the health of the banking system, which is the management quality index (i.e., productivity). For this reason, fluctuations caused by monetary policy shocks in the exchange rate, as one of the most fundamental factors affecting the health of the banking system, can have a significant negative impact. Thus, the results showed: Monetary policy shocks via exchange rate channel have a significant negative impact on the bank's profit. Monetary policy shocks via exchange rate channel have a significant positive effect on the amount of expenses in the bank. As a result, it can be said that the relationship between the monetary policy shock via exchange rate channel has a negative significant relationship with the management quality index (i.e., productivity). 5.Discussion In recent years, the exchange rate fluctuations caused by the policies of monetary and financial authorities of the country to pursue different goals and the banking-oriented nature of Iran's economy have caused the optimal management of resources and the ability of bank allocation as well as the resulting revenues to have a great impact on the country's financial performance. One of the most important indicators that can be used to attract bank resources and assess how to use resources (optimal allocation of resources) and incomes, is the productivity index in the discussion of management quality. Productivity is a combination of efficiency and effectiveness. The obtained results indicate that the impact of the monetary policy shock via exchange rate channel has increased over a certain period on the target factors. During this time, the number of changes in the target variables by the variables themselves decreases and the changes in the variables caused by the shock of the exchange rate channel increase. Therefore, monetary policy shocks through the exchange rate channel have a significant negative impact on productivity, and consequently, have a negative impact on the quality index of bank management. Moreover, monetary policy shocks through the exchange rate channel have a significant negative impact on the amount of profit earned in the bank and a significant positive effect on the amount of bank expenses.